Characterization of Lactic Acid Bacterium Exopolysaccharide, Biological, and Nutritional Evaluation of Probiotic Formulated Fermented Coconut Beverage - Bukola Christianah Adebayo-Tayo; Bukola Rachael Ogundele; Oladeji Aderibigbe Ajani; Olusola Ademola Olaniyi (International Journal of Food Science)
Exopolysaccharides (EPSs), produced by lactic acid bacteria (LAB), play a crucial role in enhancing the texture and stability of yoghurt by forming a protective matrix that helps to maintain its rheological and sensory characteristics. The search for a dairy alternative for the lactose-intolerant populace is a necessity, and the use of probiotic LAB and their EPS to formulate fermented coconut beverage (FFCB) will be of added advantage. The production and characterization of EPS from a LAB strain isolated from yoghurt, its probiotic and antioxidant potential, and its application in the production of probiotic FFCB were investigated. The EPS produced by the isolate was characterized using a scanning electron microscope (SEM), high-performance liquid chromatography, Fourier transform infrared (FT-IR) spectroscopy, and energy-dispersive X-ray. The antioxidant potential of the EPS was determined. The isolate probiotic potential, such as tolerance to low pH, bile salts, gastric pH, autoaggregation, coaggregation, antimicrobial potential, and antibacterial activity, was evaluated, and the isolate was identified using 16S rRNA. The LAB strain and the EPS were used for the formulation of probiotic FFCB, and the proximate mineral composition of the enriched yoghurt was determined. Isolate W3 produced 6204.50 mg/L EPS. The EPS produced by the LAB was spherical with a coarse surface. Hydroxyl, carboxyl, and α-pyranose were the major functional groups present in the EPS. Eight monosaccharides were present in glucose, which has the highest molar ratio. The EDX spectra ascertain the presence of carbon, oxygen (carbohydrate), and other elements. The purified EPS exhibited antioxidant activity in a dose-dependent manner. DPPH, FRAP, TAC, and TPC of the EPS ranged from 42.36% to 75.88%, 2.48 to 5.31 μg/mL, 1.66 to 3.57 μg/mL, and 1.42 to 2.03 μg/mL, respectively. The LAB strain exhibited moderate tolerance to low pH, bile salts, gastric juice, good autoaggregation (13.33%), coaggregation (0%–59.09%) with E. coli, and varied sensitivity to different antibiotics used. The isolate is hemolysis, deoxyribonuclease (DNase), and lecithinase negative, possesses characteristics of probiotics, and could have the ability to confer health benefits. The LAB strain has a 100.0% pairwise identity to Pediococcus acidilactici. The FFCB has pH, lactic acid, specific gravity, total soluble solids (TSSs), and vitamin C content ranging from 5.81 to 6.8, 10.8 to 55.8 mg/L, 0.910 to 1.394 kg/m3, 0.136 to 0.196 °Bx, and 0.26% to 0.66%. The formulated beverage fermented with a commercial starter had the highest lactic acid at Day 7 of storage. The FFCB sample with the commercial starter and the probiotic strain had the highest ash and crude fiber content (1.3%, 0.68%). The FFCB fortified with EPS showed the highest protein content (4.6%). The formulated yogurt samples fortified with the highest concentration of EPS had the highest calcium content after 7 days of storage (162.31±0.01a). In conclusion, EPS produced by Pediococcus acidilactici was a heteropolymeric EPS with good antioxidant activity, and the LAB strain exhibited a good starter for producing FFCB enriched with EPS. The FFCB has good nutritional characteristics and could serve as a functional and natural nutraceutical food for the lactose intolerance population.